Pembentukan Karakter Islami Siswa Madrasah Aliyah Hidayatullah Depok Melalui Kegiatan Ekstrakurikuler Pramuka - Hafiz Iftitah Qawly; Muhammad Abdullah Darraz (Journal on Education, 2024)
This research aims to explore in-depth the process of Islamic character formation among students at Hidayatullah Islamic Senior High School in Depok through scout extracurricular activities. It seeks to investigate the extent to which scouting activities influence a student's character, as well as identify the supporting and inhibiting factors affecting the effectiveness of these scouting activities in achieving the goal of shaping the character of Hidayatullah Islamic Senior High School students in Depok. Therefore, this research aims to contribute to a deeper understanding of the role of extracurricular activities in the process of Islamic character formation among students at Hidayatullah Islamic Senior High School in Depok. The research method used is descriptive qualitative, collecting data through observations, interviews, and analysis of documents related to scout extracurricular activities at Hidayatullah Islamic Senior High School in Depok. The results of this research indicate that scout extracurricular activities play a significant role in shaping the Islamic character of students, especially in aspects such as discipline, courage, self-confidence, honesty, responsibility, social spirit, leadership, and knowledge enhancement, particularly in religious knowledge. This research is expected to contribute to a better understanding of the Islamic character formation of Hidayatullah Islamic Senior High School students in Depok through scout extracurricular activities